Hydrocortisone effect on hyaluronate synthesis in a self‐assembled human dermal equivalent. (16th August 2013) - Deshpande, Madhura; Papp, Suzanne; Schaffer, Lana; Pouyani, Tara
Abstract: Human dermal matrix is a 'self‐assembled' dermal equivalent containing large amounts of the glycosaminoglycan hyaluronic acid (hyaluronate, hyaluronan, HA). We sought to investigate the actions of the hormone hydrocortisone on hyaluronate synthesis in the human dermal matrix. To this end, human dermal fibroblasts were cultured under serum‐free conditions, and in the absence of a three‐dimensional matrix, in the presence of varying amounts of hydrocortisone. The resultant human dermal matrices were characterized. We report that low concentrations of hydrocortisone enhance hyaluronate synthesis in the human dermal equivalent and higher concentrations cause inhibition of hyaluronate synthesis. Other glycosaminoglycan (chondroitin sulphate) synthesis is not affected by changing hydrocortisone concentrations up to 500× (200 µg/ml) of the base value. In order to gain preliminary insight into the molecular mechanism of hyaluronate inhibition, a differential gene array analysis was conducted of human dermal matrix grown in the presence of 200 µg/ml hydrocortisone and in a physiological concentration (0.4 µg/ml, normal conditions). The results of these experiments demonstrate the differential expression of 43 genes in the 500× (200 µg/ml) hydrocortisone construct as compared to the construct grown under normal conditions (0.4 µg/ml hydrocortisone). These preliminary experiments suggest that hydrocortisone at higher concentrations may exert its inhibitory effect on hyaluronate synthesis early in the glycolytic pathway, leading to HA biosynthesis by downregulation of phosphoglucomutase and glucose phosphate isomerase, possibly leading to depletion of the cellular pool of UDP‐sugar precursors necessary for HA synthesis. Copyright © 2013 John Wiley & Sons, Ltd.